The Moderating Effects of Market Orientation in the Relationship Between Supply Chain Integration and Broadband Service Performance: A Case Study in Telekom Malaysia Berhad - Syarehan, Hassan @ Md Hassan (2023)
The choice of telecommunication service provider in Malaysia is significantly influenced by lifestyle dimensions such as speed, quality, and price. Nevertheless, empirical research on the role of supply chain integration (SCI), market orientation (MO), and broadband service performance (BSP) of fixed and mobile broadband services is limited. This study investigates SCI, including supplier integration (SI), customer integration (CI), and internal integration (II) and the relationship between MO and BSP. This study uses a case study approach of a telecommunication company in Malaysia (i.e., Telekom Malaysia Berhad). Both qualitative and quantitative are used in this study. Firstly, in-depth interviews were conducted with three individuals from their top management to get a comprehensive overview of the variables in the study. Next, the results of the interviews led to the development of a questionnaire, which 188 employees of the telecommunications company answered. Data were analyzed using partial least squares-structural equation modeling (PLSSEM). The results reveal that internal integration (II) and customer integration (CI) significantly impact SCI and BSP, inferring the adaptation of supply chain management in the Malaysian telecommunication industry is relatively modest. In addition, the indirect effect of MO on the relationship between SCI and BSP was significant. The findings provide guidelines for telecommunication company to improve their BSP. This study provides significant insights into the moderating role of MO in the association between SCI and BSP among Telecom employees in Malaysia in Malaysia. Hence, it also improved the generalization concerning SCI, MO and BSP through applying resource-based view (RBV) among Telecom employees in Malaysia. It will be more interesting for future research to investigate other SCI elements toward BSP involving more telecommunication companies, or even comparative studies with other telco in different countries.